Impact of COVID-19 pandemic on behaviors in physical activity, sleep quality and usage of sport facilities in university students - Lim, Qing Feng (Nanyang Technological University, 2021)
The coronavirus disease 2019 (COVID-19) has resulted in a restriction to perform day-to-day activities, affecting physical activity participation and lifestyle changes. The purpose of this study was to investigate the impact of COVID-19 pandemic on behaviours in physical activity, sleep quality and usage of sports facilities in Singapore university students. 150 participants who were between the aged of 21 to 30 and were currently studying full time or part time in a local or private university in Singapore were recruited to take part in an online questionnaire. Of the 150 responses, 126 were deemed as valid. The online questionnaire consisted of 43-items targeting physical activity, usage of sports facilities, sleep quality and screen time usage both retrospectively and prospectively. Although 67.2% of the males and 53.2% of the females have met the physical activity guidelines, there were an overall decreased in PA participation across all categories (p < .05). Sedentary (sitting) behaviour was seen to increase by an average of 90.5 min/day (p < .001). There were also a decreased in the booking frequency in sports facilities (2.1 to 1.6, p < .001) and time spent in a sports facility (127 to 51.6 min/week, p < .001). Despite an increase in overall screen time usage (411.4 to 503.1 min/day, p < .001), there was no significant different in the overall quality of sleep (p = .0455). In times of public health emergency, strategies and interventions could be developed to encourage and promote safe physical activity participation, benefitting physical and mental well-being.